Population genetics unveils large‐scale migration dynamics and population turnover of Spodoptera exigua. Issue 2 (18th October 2021) - Wang, Xingya; Yang, Xianming; Zhou, Lihong; Wyckhuys, Kris AG; Jiang, Shan; Van Liem, Nguyen; Vi, Le Xuan; Ali, Abid; Wu, Kongming
Abstract: BACKGROUND: Migration is a widespread phenomenon among many insect species, including herbivorous crop pests. At present, scant information exists on the long‐range migration of the polyphagous armyworm, Spodoptera exigua and its underlying climatic determinants (i.e. East Asian or South Asian monsoon circulation). In this study, we employed a population genetics approach to delineate S. exigua migration patterns across multiple Asian countries. RESULTS: Using mitochondrial cytochrome I ( COI ) and microsatellite markers, low‐to‐moderate levels of genetic diversity were detected among 101 S. exigua populations collected across China, Pakistan and Vietnam. Haplotype diversity and nucleotide diversity did not differ between years. Two spatially explicit genetic clusters were detected, an eastern and a western clade, with the former comprising populations in the East Asia monsoon area. No genetic differentiation was recorded among armyworm populations in the year‐round breeding area, nor among those of the overwintering and nonoverwintering areas. Five of the most widespread mitochondrial haplotypes reflected the extensive gene flow across at a large spatial scale. CONCLUSION: Low‐to‐moderate levels of genetic diversity were observed, and evidence was found for genetic clustering in certain geographical areas. Accordingly, our unique insights into S. exigua population genetics and spatiotemporal migration dynamics help to guide applied ecological studies, ecological intensification schemes or (area‐wide) pest management campaigns in China and abroad. © 2021 Society of Chemical Industry. Abstract : In this work, we found evidence for two genetic clusters and for continent‐wide migration dynamics of Spodoptera exigua across China, Pakistan and Vietnam.